Enteroids Derived From Inflammatory Bowel Disease Patients Display Dysregulated Endoplasmic Reticulum Stress Pathways, Leading to Differential Inflammatory Responses and Dendritic Cell Maturation. (4th December 2019) - Rees, William D; Stahl, Martin; Jacobson, Kevan; Bressler, Brian; Sly, Laura M; Vallance, Bruce A; Steiner, Theodore S
Abstract: Background and Aims: Endoplasmic reticulum [ER] stress in intestinal epithelial cells [IECs] contributes to the pathogenesis of inflammatory bowel disease [IBD]. We hypothesized that ER stress changes innate signalling in human IECs, augmenting toll-like receptor [TLR] responses and inducing pro-inflammatory changes in underlying dendritic cells [DCs]. Methods: Caco-2 cells and primary human colon-derived enteroid monolayers were exposed to ATP [control stressor] or thapsigargin [Tg] [ER stress inducer], and were stimulated with the TLR5 agonist flagellin. Cytokine release was measured by an enzyme immunoassay. ER stress markers CHOP, GRP78 and XBP1s/u were measured via quantitative PCR and Western blot. Monocyte-derived DCs [moDCs] were cultured with the IEC supernatants and their activation state was measured. Responses from enteroids derived from IBD patients and healthy control participants were compared. Results: ER stress enhanced flagellin-induced IL-8 release from Caco-2 cells and enteroids. Moreover, conditioned media activated DCs to become pro-inflammatory, with increased expression of CD80, CD86, MHCII, IL-6, IL-15 and IL-12p70 and decreased expression of CD103 and IL-10. Flagellin-induced IL-8 production correlated with DC activation, suggesting a common stress pathway. Moreover, there were distinct differences in cytokine expression and basal ER stress between IBD and healthy subject-derived enteroid monolayers, suggesting a dysregulated ER stress pathway in IBD-derived enteroids. Conclusions: Cellular stress enhances TLR5 responses in IECs, leading to increased DC activation, indicating a previously unknown mechanistic link between epithelial ER stress and immune activation in IBD. Furthermore, dysregulated ER stress may be propagated from the intestinal epithelial stem cell niche in IBD patients.